Pengaruh Kualitas Produk, Promosi, dan Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Studi pada Dealer Motor Honda PT. Tirto Agung Porong - Moh. Bachrul Rizki; Rizky Eka Febriansah; Alshaf Pebrianggara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to analyze the influence of product quality, brand image, and price perception on the consumer decision-making process for purchasing Honda motorcycles. The population of this study consists of all residents of Sidoarjo. The sample was determined using the Lameshow formula, resulting in a sample size of 96.04, which was rounded up to 100 respondents. This study employed a non-probability sampling technique, specifically accidental sampling. The variables studied include product quality, promotion, and brand image. The t-test results show that product quality has a positive and significant effect on motorcycle purchasing decisions, promotion has a positive and significant effect on motorcycle purchasing decisions, and brand image also has a positive and significant effect on motorcycle purchasing decisions at the Tirto Agung Porong Dealership.